Modeling the Subscription Ratio and IPO Returns Non-Linear Relationship: Evidence from the Tunisian Stock Market - Mellouli, Dhoha; Ellouz, Siwar (International Journal of Economics and Financial Issues, 2023)
To capture the herd behavior of IPO investors, the relationship binding IPO underpricing and the subscription ratio is often assumed to represent a straight line in the relevant literature, due mainly to recurrent general linear modeling in the data analysis process. In Tunisia, however, and following the subscription result declaration, all IPOs are usually met with noticeable success owing to over subscription issues, resulting in persistent herd behavior. In this context, the present paper is deigned to highlight how Tunisian investors tend to mimic each other on setting out to make trading decisions. More particularly, we attempt to specify the non-linear relationship binding the subscription ratio and IPO returns within a quantile regression, highlighting the investors’ noticeable sensitivity to high subscription, thereby, easily inducing the spread of herd behavior and increasing IPO returns.